Health education for prevalent problems in prison, Ocaña-I proyect (Spain) - C. Maestre-Miquel; C. Zabala-Baños; J.A. García; J.M. Antolín
Objective: Pilot project focusing on the implementation and evaluation of a health education (HE) program for inmates of the prison of Ocaña I (Spain). The objective was to analyze the intentions for change in health habits and perceptions, and to assess whether the HE-program had differential effects depending on whether the participants belonged to the PAIEM or not and their socio-demographic characteristics. Methodology: The participants were 65 men, who answered an ad hoc questionnaire at the end of each session. Data analysis applied was univariate and bivariate (one-way ANOVA, t-test for Equality of Means and Chi-Square test). Results: The average rating of the sessions was 3.51 out of 4 (SD = 0.62). The percentage of positive answers about the intention to adopt healthy habits was higher among non-PAIEM subjects (84.8%) than among those who were part of this program (57.9%). All subjects having a couple indicated an intention to change negative habits, compared to 67.3% for those without a couple. The percentage of subjects who said that their perception on the issue had changed was highest among those without education (89.7%) than among those with education (61.5%). Conclusions: The evaluation of implanted HE-program implemented in the Ocaña I prison was very positive, there are differences between subjects belonging to the PAIEM and those who do not.